Caring for the healthcare professional: A description of the Schwartz Rounds™ implementation. Issue 3 (21st May 2018) - Adamson, Keith; Searl, Nancy; Sengsavang, Sonia; Yardley, John; George, Mark; Rumney, Peter; Hunter, Judy; Myers-Halbig, Sakeena
Abstract : Purpose: Hospitals must systematically support employees in innovative ways to uphold a culture of care that strengthens the system. At a leading Canadian academic pediatric rehabilitation hospital, over 90 percent of clinicians viewed Schwartz Rounds™ (SR) as a hospital priority, resulting in its formal implementation as a quality improvement initiative. The purpose of this paper is to describe how the hospital implemented SR to support the socio-emotional impact of providing care. Design/methodology/approach: This quantitative descriptive study provides a snapshot of the impact of each SR through online surveys at four assessment points (SR1-SR4). A total of 571 responses were collected. Findings: All four SR addressed needs of staff as 92.9-97.6 percent of attendees reported it had a positive impact, and 96.4-100 percent of attendees reported each SR was relevant. Attendees reported significantly greater communication with co-workers after each SR ( p <0.001) and more personal conversations with supervisors after SR2 and SR4 ( p <0.05) compared to non-attendees. Attending SR also increased their perspective-taking capacity across the four SR. Practical implications: As evidenced in this quality improvement initiative, SR addresses staff's need for time to process the socio-emotional impacts of care and to help reduce those at risk for compassion fatigue. SR supports and manages the emotional healthcare culture, which has important implications for quality patient care. Originality/value: This research details an organization's process to implement SR and highlights the importance of taking care of the care provider.